La atención temprana en el desarrollo del lenguaje oral en niños y niñas de 4 – 5 años con discapacidad intelectual leve que asisten al centro de rehabilitación “Senderos de Alegría” de la ciudad de Loja, período marzo – septiembre 2013 - Alvarado Romero, Jenny Patricia (2014)
To make it possible it was formulated as its general objective: To determine the influence in The Oral Language. The methods used were scientific, analyticsynthetic, inductive-deductive, statistical. The technique used was: Interview, applied to the therapist in charge of this area and the instrument was The Navarra Test of Oral Language that was applied to children, I work with a sample of 5 children with disabilities with intellectual disability and 6 professionals from the center, the same that were taken for the sample. Using these results, it was determined that children with mild intellectual disability who attend the center Paths of Joy are located with 80% at a level of delayed language development, placing them with early care that children receive weekly, valuations are performed at times, attendance is individual, not using any method mentioned “Quimester” planned activities; so it is recommended: that therapists work with exercises designed to stimulate oral language level of children, using a correct and proper language components. Using an appropriate early intervention, as this will help the children in the future development.To make it possible it was formulated as its general objective: To determine the influence in The Oral Language. The methods used were scientific, analyticsynthetic, inductive-deductive, statistical. The technique used was: Interview, applied to the therapist in charge of this area and the instrument was The Navarra Test of Oral Language that was applied to children, I work with a sample of 5 children with disabilities with intellectual disability and 6 professionals from the center, the same that were taken for the sample. Using these results, it was determined that children with mild intellectual disability who attend the center Paths of Joy are located with 80% at a level of delayed language development, placing them with early care that children receive weekly, valuations are performed at times, attendance is individual, not using any method mentioned “Quimester” planned activities; so it is recommended: that therapists work with exercises designed to stimulate oral language level of children, using a correct and proper language components. Using an appropriate early intervention, as this will help the children in the future development.